FAKTOR PENYEBAB RENDAHNYA MINAT SISWA MELANJUTKANKEPENDIDIKAN TINGGI (STUDI KASUS PADA SISWA DI DESA RESNO KECAMATAN V KOTO KABUPATEN MUKO-MUKO) - Sinta, Sinta Fita Yuliana; Melia, Yenni; Isnaini, Isnaini (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
ABSTRACT Based on results of The research that has been done, it was found that the factors causing the low interest of students in continue higher education in students in the Resno Village, sub-district V Koto, muko-muko District, obtained the following conclusions: 1). Internal factors cause the low interest of village youthon higner education in the Resno Village are the desire to work for money, lack of awareness/motivation to the importance of higher education, non-existent laerning/cognitive abilities and parental mindset, 2). External factors causing the low interest of village youth towards higner education in resno Village are the influences and economic conditions that are diffrent (increasing) from before. The low awareness of teenagers in the Resno Village towards education at the university the height is influenced by the behavior patterns of children and the motivation of the teenagers themselve.